1992
DOI: 10.1056/nejm199207093270202
|View full text |Cite
|
Sign up to set email alerts
|

An Imbalance between the Excretion of Thromboxane and Prostacyclin Metabolites in Pulmonary Hypertension

Abstract: An increase in the release of the vasoconstrictor thromboxane A2, suggesting the activation of platelets, occurs in both the primary and secondary forms of pulmonary hypertension. By contrast, the release of prostacyclin is depressed in these patients. Whether the imbalance in the release of these mediators is a cause or a result of pulmonary hypertension is unknown, but it may play a part in the development and maintenance of both forms of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
605
0
20

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,079 publications
(639 citation statements)
references
References 27 publications
14
605
0
20
Order By: Relevance
“…This suggests that the imbalance in prostanoids is involved in the development and persistence of pulmonary hypertension. It is assumed that endothelial damage which is inevitably accompanied by remodeling or organic change causes a deterioration ofPGI2 production in patients with pulmonary hypertension, as the vascular beds in pulmonaryarteries and/or arterioles are considered to be the main sites producing PGI2 (1)(2)(3)(4)(5). However, it has not been clearly determined whether pulmonary vascular beds responsible for the production of PGI2are functionally preserved or not in OSAS.Sheer stress in pulmonary vascular beds can be observed in various kinds of physiological and pathological situations such as hypoxic pulmonary vasoconstriction (HPV) and increased cardiac output.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the imbalance in prostanoids is involved in the development and persistence of pulmonary hypertension. It is assumed that endothelial damage which is inevitably accompanied by remodeling or organic change causes a deterioration ofPGI2 production in patients with pulmonary hypertension, as the vascular beds in pulmonaryarteries and/or arterioles are considered to be the main sites producing PGI2 (1)(2)(3)(4)(5). However, it has not been clearly determined whether pulmonary vascular beds responsible for the production of PGI2are functionally preserved or not in OSAS.Sheer stress in pulmonary vascular beds can be observed in various kinds of physiological and pathological situations such as hypoxic pulmonary vasoconstriction (HPV) and increased cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that thromboxane A2 (TxA2) is a vasoconstrictor as well as a potent stimulus for platelet aggregation which can be antagonized by the vasodilator prostacyclin (PGI2) (1)(2)(3)(4)(5). It is also suggested thatthere is apathophysiological link between systemic hypertension and obstructive sleep apnea syndrome (OSAS) (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported encouraging results with the use of repeated infusions of prostaglandin in primary pulmonary hypertension (14), but the efficacy of this approach is still uncertain, and there is insufficient experience to determine optimum therapy in secondary cases. The response to prostacyclin may, however, implicate different pressor mechanisms operating in the pulmonary and systemic circulations (15).…”
Section: Discussionmentioning
confidence: 99%
“…Prostacyclin production appears to increase in late gestation and early postnatal life [65,66], indicating its importance in promoting the neonatal pulmonary vascular transition. Pulmonary hypertension in both neonates and older children is characterized by an decrease in the biosynthesis of prostacyclin accompanied by increased synthesis of the vasoconstrictor thromboxane A 2 [67]. Furthermore, the PGI 2 receptor (IP) is decreased in adult and pediatric patients with pulmonary hypertension, and animal studies point to its contribution to altered vasodilation in PPHN [68].…”
mentioning
confidence: 99%